2013
DOI: 10.5535/arm.2013.37.4.582
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum Sacral Stress Fracture Mimicking Lumbar Radiculopathy in a Patient With Pregnancy-Associated Osteoporosis

Abstract: Postpartum sacral fracture is relatively rare, and its diagnosis is often delayed. We herein report such a case of a 28-year-old patient who presented with an insidious-onset lower back pain, left buttock pain, and radicular symptoms mimicking lumbar radiculopathy. Laboratory tests showed a decreased 25-hydroxy vitamin D level, and the bone mineral densitometry of both femurs was below the expected range. Plain radiographs of the lumbar spine and pelvis showed no definite abnormality, but lumbosacral spinal ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 9 publications
0
15
1
Order By: Relevance
“…A review by Kahanov et al found that ∼95% of patients with sacral stress fractures initially presented with lower back pain or buttock pain and that neurologic symptoms were an uncommon presenting complaint with radicular symptoms occurring in only 2% of cases. 17 18 Back pain symptoms are typically localized to one sacral area, worse with standing or activity, and relieved by rest or lying flat, and they may be associated with strenuous impact activities in cases of SFF. Although no physical examination features are specific to sacral stress fractures, findings include an antalgic gait, localized tenderness over the sacral paraspinal area, and positive clinical tests that include the Gaenslen test, squish test, or Patrick test.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A review by Kahanov et al found that ∼95% of patients with sacral stress fractures initially presented with lower back pain or buttock pain and that neurologic symptoms were an uncommon presenting complaint with radicular symptoms occurring in only 2% of cases. 17 18 Back pain symptoms are typically localized to one sacral area, worse with standing or activity, and relieved by rest or lying flat, and they may be associated with strenuous impact activities in cases of SFF. Although no physical examination features are specific to sacral stress fractures, findings include an antalgic gait, localized tenderness over the sacral paraspinal area, and positive clinical tests that include the Gaenslen test, squish test, or Patrick test.…”
Section: Discussionmentioning
confidence: 99%
“…Although no physical examination features are specific to sacral stress fractures, findings include an antalgic gait, localized tenderness over the sacral paraspinal area, and positive clinical tests that include the Gaenslen test, squish test, or Patrick test. 17 If present, the commonest radiculopathies involve the S1 or S2 distribution. 19 Unfortunately, the differential diagnosis for lower back pain is extensive and includes musculoskeletal sprains, lumbar disk disease, facet arthropathy, sacroiliac joint pathologies, spondyloarthropathies, spondylolysis, spinal stenosis, and neoplasms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Axial loading of the spine may compress intervertebral discs, reduce disc height and cause disc protrusion culminating in radicular symptoms. Osteoporosis in pregnancy has been associated with vertebral [48] and sacral stress fractures [60] . Other rare pathologies may include osteomyelitis [99] and spinal tumours [91,100] .…”
Section: Discussionmentioning
confidence: 99%